M5 Neural networks linked to emotion processing modulated by intranasal oxytocin in huntington's disease gene-carriers. (13th September 2016) - Labuschagne, Izelle; Poudel, Govinda; Kordsachia, Catarina; Wu, Qizhu; Thomson, Hannah; Georgiou-Karistianis, Nellie; Churchyard, Andrew; Stout, Julie
Abstract : Background: Oxytocin (OXT) has shown to play an important role in modulating responses to emotional cues in healthy and clinical populations. Huntington's disease (HD) is associated with deficits in facial expressions of emotion, particular of disgust, and which have been linked to abnormal neural networks. HD is also associated with a 45% reduction in OXT-expressing neurons in the hypothalamus, the region where OXT is produced. Aims: We therefore examined whether administration of OXT intranasally to gene-carriers of HD would have beneficial effects on neural networks involved in emotion processing. Methods: We compared 9 gene-carriers of HD and 10 age-matched controls, who were right-handed males, aged between 18–65 years, not medicated, and non-smokers. Using a randomised double-blind placebo-controlled design, each participant administered acute doses of intranasal OXT (24 IU) and placebo sprays over two visits. Participants completed an fMRI task involving matching emotional faces (disgust, happy, anger, fear, sad, surprise and neutral) or geometric shapes. Results: Under placebo, and compared to controls, HD gene-carriers showed hypo-activity to disgust (middle/superior prefrontal gyrus) and hyper-activity to surprise (inferior/middle temporal gyrus). Significant Group x Drug interactions was found for five of the seven emotions (angry, disgust, fear, happy and sad). Post-hoc analyses showed significant within-group effects, corrected for multiple comparisons, where OXT significantly increased brain reactivity for happy (middle temporal gyrus) and disgust (precentral/inferior frontal gyrus) in the HD group. Conclusions: We found evidence of hypo- and hyper-reactivity to disgust and surprise emotions respectively in HD gene-carriers. OXT increased brain activity in previously hypo-active regions in HD. We provide initial evidence of 'normalisation' effects and a broader physiological role of OXT in HD.